MENINGKATKAN LITERASI WIRAUSAHA TENTANG KULINER HALAL MELALUI SOSIALIASI PADA MASYARAKAT - Febrian Maulana Putra; Syamsul Hilal; Hanif Hanif (Jurnal Abdimas Bina Bangsa, 2024)
The emergence of halal cuisine among local and international communities presents significant prospects for the economic advancement of the Province of Lampung. Consequently, it is imperative for the general public to comprehend the significance of halal gastronomy. The purpose of this commitment to the community is to provide information to the general public on halal cuisine. This activity employs a methodology that encompasses three distinct stages: planning, implementation, and evaluation. The delivery of this devotional practice is facilitated through the use of lectures. The anticipated outcomes of these endeavors are projected to have a favorable impact on enhancing the literacy of entrepreneurs in the domain of halal culinary, hence enabling the community to foster sustainable development in halal cuisine. The implications of these actions can serve as a valuable resource for governments, educational institutions, and industry stakeholders to improve their comprehension and entrepreneurial abilities in the culinary field, particularly in regards to halal cooking principles